Bioactive terpenoids from the stem bark of Entada spiralis Ridl.(Sintok) - Harun, Aiza; Mat So'ad, Siti Zaiton; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini (2012)
The application of Entada sipralis Ridl. (Leguminoceae) stem bark containing saponin in the treatment of scalp and as body soap is well known for generations. Our previous investigation revealed E. spiralis stem bark contains several of terpenoid compounds and are responsible for the inhibitory effect against bacteria Staphyloccus epidermis ATCC 12228 and skin disease dermatophytes, Microsporum gypseum ATCC 24102, Trichophyton mentagrophytes ATCC 9533 and Trichophyton tonsurans ATCC 28942. The aim of this work is to isolate and identify the chemical structure of some terpenoid compounds from the active fraction of E. spiralis stem bark. The isolation of active compounds was conducted by means of chromatographic separation, and the structure characterization was done based on spectroscopic analysis (1H,13C NMR, HMQC, HMBC and DEPT135) and comparison with those of the literature. We managed to isolate two terpenoid compounds known as ester saponin (1) and terpene benzoate (2). The extensive 1D and 2D Nuclear Magnetic Resonans (NMR) experiments identified (1) as 16-β-D-arabinofuranosyl-15-β-D-xylopyranosyl-5,8,9,10-tetrahydroxyl-17,18,19,20-tetramethyl diterpene ester and (2) as 4-(β-D-glucopyranosyl)-1-hydroxybenzene-(20-hydroxyl-18,19dimethylcyclotetradecanol) benzoate. The isolation and characterization of (1) and (2) is hoped to give new impact on the search of new natural antimicrobial drug as the compounds are not pharmacologically and chemically investigated to date.